2012
DOI: 10.1177/1524838012447698
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to Posttraumatic Stress Disorder in Adolescence

Abstract: Studies of posttraumatic stress disorder (PTSD) in adolescence published from 2000 to 2011 indicate that adolescents are at greater risk of experiencing trauma than either adults or children, and that the prevalence of PTSD among adolescents is 3-57%. Age, gender, type of trauma, and repeated trauma are discussed as factors related to the increased rates of adolescent PTSD. PTSD in adolescence is also associated with suicide, substance abuse, poor social support, academic problems, and poor physical health. PT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
107
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 145 publications
(128 citation statements)
references
References 93 publications
19
107
0
2
Order By: Relevance
“…More than half (59.2%) of the participants received psychotherapy (mainly cognitive and be havioural therapy and play therapy), while 36.7% received a combination of psychotherapy and medication. This approach is in line with current policy to treat PTSD in children and adolescents with a combination of psychotherapy [19,24,29,30] and medication. [29,30] …”
Section: Associated Stressorssupporting
confidence: 66%
See 2 more Smart Citations
“…More than half (59.2%) of the participants received psychotherapy (mainly cognitive and be havioural therapy and play therapy), while 36.7% received a combination of psychotherapy and medication. This approach is in line with current policy to treat PTSD in children and adolescents with a combination of psychotherapy [19,24,29,30] and medication. [29,30] …”
Section: Associated Stressorssupporting
confidence: 66%
“…[18] Adolescents face a number of new phase-specific developmental demands including the acquisition of coherent identities, establishing relations with peers and developing independence from parents. [19] International studies have also highlighted high rates of traumatisation and PTSD in children and adolescents. For example, Holford et al [20] reported that 25 -100% of children and adolescents exposed to sudden unanticipated violence develop PTSD.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Les manifestions cliniques de ce trouble comprennent des symptômes d'intrusion, d'évitement des stimuli associés à l'événement traumatisant et d'hyperéveil. Ainsi, parmi l'éventail des répercussions associées à l'agression sexuelle vécue pendant l'enfance, les SSPT sont parmi les plus fréquemment retrouvés chez les victimes d'agression sexuelle (Oddone Paolucci, Genuis et Violato, 2001), avec 57 % des adolescents présentant un historique d'agression sexuelle qui souffrent de SSPT atteignant le seuil clinique (Nooner et al, 2012). L'adolescence constituerait une période critique pour le développement des SSPT.…”
Section: Symptômes De Stress Post-traumatiqueunclassified
“…L'adolescence constituerait une période critique pour le développement des SSPT. En effet, les jeunes sont exposés à plus d'événements traumatiques que les adultes et présentent des taux de SSPT plus élevés que ces derniers (Nooner et al, 2012). Sur le plan des différences liées au genre, si certaines observations indiquent que les filles présentent des taux d'état de stress post-traumatique deux fois plus élevés que les garçons (Kilpatrick et al, 2003 ;Nooner et al, 2012), d'autres semblent indiquer que les garçons et les filles présentent des taux équivalents (Maikovich, Koenen et Jaffee, 2009).…”
Section: Symptômes De Stress Post-traumatiqueunclassified